2020
DOI: 10.1111/jocd.13500
|View full text |Cite
|
Sign up to set email alerts
|

Collagen formula with Djulis for improvement of skin hydration, brightness, texture, crow’s feet, and collagen content: A double‐blind, randomized, placebo‐controlled trial

Abstract: Background: The efficacy of Djulis for skin care is currently based on cellular or animal models, and the clinical aspect is not in place. Aim: This clinical study is to investigate the synergistic effect of fish collagen and Djulis (Chenopodium formosanum Koidz.) for improvement of skin parameters. We used the combination of hydrolyzed collagen and Djulis to develop a new functional formula for skin improvement. Patients/Methods: Fifty volunteers were randomly allocated (in a 1:1 ratio) to the placebo or coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…High-resolution analysis combined with a score method was also used here to evaluate skin pores. The results showed that hydrolyzed fish cartilage supplementation was effective in reducing skin pores, in agreement with Lin et al, (2020) [ 26 ], who showed that oral supplementation with collagen can be effective in reducing pores and wrinkles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High-resolution analysis combined with a score method was also used here to evaluate skin pores. The results showed that hydrolyzed fish cartilage supplementation was effective in reducing skin pores, in agreement with Lin et al, (2020) [ 26 ], who showed that oral supplementation with collagen can be effective in reducing pores and wrinkles.…”
Section: Discussionsupporting
confidence: 89%
“…RCM analysis showed an improvement of the RCM descriptors related to the dermis in the group that used the oral hydrolyzed fish cartilage supplement, in agreement with the results obtained in the analysis of dermis echogenicity, which was improved after the use of the hydrolyzed fish cartilage supplement for 90 days. In addition, although there have been some studies showing an improvement in dermis echogenicity after supplementation with collagen peptides [ 8 , 12 , 26 ], the application of RCM to the evaluation of skin morphological and structural characteristics after oral supplementation has not been previously investigated. Thus, RCM collagen analysis can be used as a supporting method for dermis evaluation in combination with other imaging techniques such as high frequency ultrasound analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[8,27] Clinical trials have indicated that the intake of red djulis can increase collagen and skin hydration by improving the adhesion of keratinocytes. [11,28] Therefore, unhulled red djulis extracts affected the gene expressions related to skin barrier, antioxidation, and collagen, and showed positive effects on skin barrier integrity, endogenous antioxidant activity, and skin collagen preservation.…”
Section: Unhulled Red Djulis Extracts Regulated Skin-related Genes Antioxidant-related Genes and Collagen-related Genesmentioning
confidence: 98%
“…[9] Red dijulis extract has antioxidant and moisturizing effects, and can stimulate the proliferation of fibroblasts and keratinocytes during wound healing and regeneration [9,10] In addition, previous study has shown that red djulis can delay the skin aging process and improve skin aging parameters in subjects with poor skin condition. [11] Thus, red djulis has the potential to improve skin conditions. However, the anti-glycation, anti-oxidation on skin cells, and the influences of the effective components in djulis still were not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Djulis is an undervalued traditional crop belonging to the genus Chenopodium and class of Dicotyledoneae , which is typically grown in aboriginal regions of Taiwan (Huang et al ., 2019). In recent years, many studies have highlighted the djulis and its by‐products as an emerging novel source of functional ingredients, such as bioactive compounds (Sun et al ., 2019), in vivo anti‐diabetes (Li et al ., 2021) and improvement of skin hydration (Lin et al ., 2021). Moreover, utilisation of djulis hulls, seedlings and leaves have been found to have additional health benefits, indicating the waste valorisation approaches to minimise the environmental impacts.…”
Section: Introductionmentioning
confidence: 99%